Investigation into the interactions of supercritical argon as a solvent with trans-1,2-dichloroethylene using ultraviolet-visible and infrared spectroscopy : a thesis presented in partial fulfilment of the requirements for the degree of Masters of Science in Chemistry at Massey University, Auckland, New Zealand - Moffet, Erin Sarah (Massey University, 2018)
This thesis looks at the uses and interactions of argon as a solvent at or above its supercritical temperature and pressure. A supercritical fluid allows for a range of properties depending on where the conditions of pressure and temperature are in relation to the critical point of the chosen substance. These supercritical fluids have been shown to be useful across many areas of industry and research and are the ideal fluid to use in a molecular beam pulsed valve. Solubility interactions of argon and trans-1,2-dichloroethylene (DCE) across multiple conditions were monitored using ultraviolet-visible (UV-Vis) and infrared (IR) spectroscopy. Two high pressure cells were designed, constructed and tested to withstand the 50 atmospheres and 140 K conditions required. The initial cell focused on UV-Vis spectroscopy with the DCE vapour showing an exponential decrease in absorbance as the temperature in the cell was reduced. Changing conditions to reach the supercritical region of argon resulted in a significant increase in the absorbance and therefore the solubility of DCE. The second cell constructed focuses on analysis using infrared spectroscopy and showed clear peak shifts and shape changes at the bᵤ CH stretch (v₉) and bᵤ CH bend (v₁₀) for trans-1,2-dichloroethylene (DCE) The intensity at aᵤ CH bend (v₆) and bᵤ CCl stretch (v₁₁) proved to be less informative. DCE vapour acted predictably as the temperature was reduced, resulting in a significant drop off in absorbance similar to that observed in the UV-Vis. In changing to the supercritical and liquid argon conditions resulted in the appearance of an asymmetric lineshape characteristic of Fano resonance, which is not common in infrared spectroscopy. This suggest that there is an interaction occurring between a discrete state of DCE that couples to a background continuum process. This Fano resonance does not appear to be present in an argon matrix isolation.
Keywords: Argon; Supercritical fluids; Solvents; Dichloroethylene; Ultraviolet spectroscopy; Infrared spectroscopy; Spectrum analysis